Clinical significance of synovial lymphoid neogenesis and its reversal after anti-tumour necrosis factor α therapy in rheumatoid arthritis. Issue 5 (21st May 2008) - Cañete, J D; Celis, R; Moll, C; Izquierdo, E; Marsal, S; Sanmartí, R; Palacín, A; Lora, D; de la Cruz, J; Pablos, J L
Abstract : Objective: To investigate the clinical significance of lymphoid neogenesis (LN) in rheumatoid arthritis (RA), the clinicopathological correlates of this process and its evolution after anti-tumour necrosis factor (TNF)α therapy in a large series of synovial tissues were analysed. Methods: Arthroscopic synovial biopsies from 86 patients with RA were analysed by immunohistochemistry. LN was defined as the presence of large aggregates of lymphocytes with T/B cell compartmentalisation and peripheral node addressin (PNAd) positive high endothelial venules. Clinical variables at baseline and after prospective follow-up were compared in LN positive and negative RA subsets. The evolution of LN and its correlation with the clinical course in a subgroup of 24 patients that underwent a second arthroscopic biopsy after anti-TNFα therapy was also analysed. Results: LN was present in 49% of RA synovial tissues. Patients with LN had a significantly higher disease duration and a higher previous use of anti-TNFα agents. During prospective follow-up, the proportion of patients achieving good or moderate European League Against Rheumatism (EULAR) 28-joint Disease Activity Score (DAS28) responses was significantly lower in patients who were LN positive despite a significantly higher use of anti-TNFα agents. By multivariate logistic regression analysis, LN remained as an independent negative predictor of response to therapy. In the subgroup of patients rebiopsied after anti-TNFα therapy, reversal of LN features occurred in 56% of the patients and correlated with good clinical responses. Conclusions: Synovial LN in RA predicts a lower response to therapy. LN features can be reversed after a short period of anti-TNFα therapy in parallel to good clinical responses.